Snowman - Nesbo, Jo 1960-; Bartlett, Don (London : Vintage Crime/Black Lizard, 2012)
One night, after the first snowfall of the year, a boy wakes up and discovers that his mother has disappeared Inspector Harry Hole suspects a link between the missing woman and a suspicious letter he's received. but a patter emerges: for a decade, eleven women have vanished, all on the fie day of the first snow.
108272
Keywords: Mystery fiction -- Murder -- Serial killers -- Detectives -- Norway; Thriller fiction